Growing rations of forage sorghum silage and alfalfa haylage - Ilg, H.; Bolsen, K.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Growing rations containing forage sorghum silage (FSS) or equal amounts of FSS and alfalfa haylage were fed to crossbred steer calves for 112 days. Steers consumed more of the FSS + haylage but rate and efficiency of gain were best for steers fed the FSS. We calculated the value of alfalfa haylage at various prices for FSS and soybean meal.
Keywords: Beef; Rations; Sorghum silage; Alfalfa haylage